Using pattern mining to determine fine climatic parameters for maize yield in Benin - Gloria Tahi, Souand Peace; Ratheil Houndji, Vinasetan; Gbêmêmali Hounmenou, Castro; Glèlè Kakaï, Romain (Institute of Advanced Engineering and Science, 2024)
This study investigates the relationships between Benin's climate and maize production to develop an association rule algorithm for accurate yield prediction. The datasets utilized extend 26 years (1995 to 2020) and include climate and maize yield data from five districts with synoptic weather stations in two agroclimatic zones (Sudanian and Sudano-Guinean). Climate variables were combined with yield using